Bridging Gaps in Health Access Through Telehealth in Indonesia: A Literature Review Focused on Primary Care - Okta, Setyo Luthfi; Jaizul, Alim (International Journal of Health, Medicine, and Sports, 2025)
Indonesia, the world's largest archipelagic nation, faces significant challenges in equitable access to healthcare services, particularly in remote areas. Telehealth presents a potential solution to bridge this gap, particularly in primary healthcare. This study aims to examine the effectiveness, accessibility, and readiness of Indonesia's primary healthcare system to adopt telehealth, based on a review of international and national scientific literature. The study results indicate that telehealth can improve service effectiveness by accelerating diagnosis, improving referral mechanisms, and interprofessional collaboration. Healthcare worker satisfaction also increases, particularly when supported by adequate digital infrastructure. However, telehealth adoption remains unequal, with users concentrated in urban areas and groups with high digital literacy. Other challenges identified include uneven digital infrastructure, inadequate healthcare worker training, and the absence of regulations guaranteeing data security and electronic medical record (EHR) interoperability. While there is potential for leveraging technologies such as artificial intelligence to improve service efficiency, the success of this transformation depends on inclusive regulations and cross-sectoral leadership. Therefore, telehealth must be viewed not merely as a technological innovation, but as a tool for systemic transformation that requires readiness in infrastructure, regulations, human resources, and community participation.